A look at actions: direct gaze modulates functional connectivity of the right TPJ with an action control network. Issue 9 (8th October 2019) - Zillekens, Imme Christina; Schliephake, Lena Maria; Brandi, Marie-Luise; Schilbach, Leonhard
ABSTRACT: Social signals such as eye contact and motor actions are essential elements of social interactions. However, our knowledge about the interplay of gaze signals and the control of actions remains limited. In a group of 30 healthy participants, we investigated the effect of gaze (direct gaze vs averted) on behavioral and neural measures of action control as assessed by a spatial congruency task (spatially congruent vs incongruent button presses in response to gaze shifts). Behavioral results demonstrate that inter-individual differences in condition-specific incongruency costs were associated with autistic traits. While there was no interaction effect of gaze and action control on brain activation, in a context of incongruent responses to direct gaze shifts, a psychophysiological interaction analysis showed increased functional coupling between the right temporoparietal junction, a key region in gaze processing, and the inferior frontal gyri, which have been related to both social cognition and motor inhibition. Conversely, incongruency costs to averted gaze were reflected in increased connectivity with action control areas implicated in top-down attentional processes. Our findings indicate that direct gaze perception inter-individually modulates motor actions and enforces the functional integration of gaze-related social cognition and action control processes, thereby connecting functional elements of social interactions.